Insomnia and cognitive behavioural therapy—how to assess your patient and why it should be a standard part of care - Anderson, Kirstie N. (Journal of Thoracic Disease; Vol 10, Supplement 1 (January 24, 2018): Journal of Thoracic Disease (Dedicated to the 3rd Clinical Update Sleep: International Conference 2018, Endorsed by ERS), 2018)
Hippocrates recognized the importance of asking about sleep as long ago as 400 BC when he wrote “sleep and watchfulness, both of them when immoderate, constitute disease”. Disrupted sleep for any reason has immediate and long term consequences on physical and mental health. Insomnia disorder (“immoderate watchfulness”) remains the commonest sleep disorder in primary and secondary care with an estimated 5–10% of the adult population affected. While it is commonly comorbid with other physical and mental health problems, the new diagnostic classification has been helpfully simplified such that it is considered a disorder in itself. If it is the patient’s main concern, it warrants treatment. Patients and health professionals have often had limited teaching about effective strategies for insomnia which leaves many untreated and insomnia can be unfairly perceived as a challenging symptom to manage. The first line treatment is now well established as insomnia-specific cognitive behavioural therapy (CBTi) in the most recent US and European treatment guidelines. Over 25 years of high quality research have shown evidence for sustained improvements in sleep in those with insomnia alone or insomnia comorbid with other conditions. This is a simple CBT to deliver with better and safer outcomes than prescription hypnotics. Therefore, this review will cover the initial assessment of insomnia, including insomnia mimics, the selection of patients for treatment and the key components of CBT therapy. Finally, the review will cover evidence for different modes of delivery (online, self, help, group or individual face to face) in a variety of clinical settings.